Molecular characterization of a Toxocara variant from cats in Kuala Lumpur, Malaysia - Zhu, Xing Quan; Jacobs, Dennis E.; Chilton, Neil B.; Abdullah Sani, Rehana; Cheng, Nadzariah A. B. Y.; Gasser, Robin B. (Cambridge University Press, 1998)
The ascaridoid nematode of cats from Kuala Lumpur, Malaysia, previously identified morphologically as Toxocara canis, was characterized using a molecular approach. The nuclear ribosomal DNA (rDNA) region spanning the first internal transcribed spacer (ITS-1), the 5.8S gene and the second internal transcribed spacer (ITS-2) was amplified and sequenced. The sequences for the parasite from Malaysian cats were compared with those for T. canis and T. cati. The sequence data showed that this taxon was genetically more similar to T. cati than to T. canis in the ITS-1, 5.8S and ITS-2. Differences in the ITS-1 and ITS-2 sequences between the taxa (9.4-26.1%) were markedly higher than variation between samples within T. canis and T. cati (0-2.9%). The sequence data demonstrate that the parasite from Malaysian cats is neither T. canis nor T. cati and indicate that it is a distinct species. Based on these data, PCR-linked restriction fragment length polymorphism (RFLP) and single-strand conformation polymorphism (SSCP) methods were employed for the unequivocal differentiation of the Toxocara variant from T. canis and T. cati. These methods should provide valuable tools for studying the life-cycle, transmission pattern(s) and zoonotic potential of this parasite.